A Xenopus oocyte β subunit: Evidence for a role in the assembly/expression of voltage-gated calcium channels that is separate from its role as a regulatory subunit - Tareilus, Erwin (The National Academy of Sciences of the USA, 1997)
Two closely related β subunit mRNAs (xo28 and xo32) were identified in Xenopus oocytes by molecular cloning. One or both appear to be expressed as active proteins, because: (i) injection of Xenopus β antisense oligonucleotides, but not of sense or unrelated oligonucleotides, significantly reduced endogenous oocyte voltage-gated Ca(2+) channel (VGCC) currents and obliterated VGCC currents that arise after injection of mammalian α(1) cRNAs (α(1C) and α(1E)); (ii) coinjection of a Xenopus β antisense oligonucleotide and excess rat β cRNA rescued expression of α(1) Ca(2+) channel currents; and (iii) coinjection of mammalian α(1) cRNA with cRNA encoding either of the two Xenopus β subunits facilitated both activation and inactivation of Ca(2+) channel currents by voltage, as happens with most mammalian β subunits. The Xenopus β subunit cDNAs (β3xo cDNAs) predict proteins of 484 aa that differ in only 22 aa and resemble most closely the sequence of the mammalian type 3 β subunit. We propose that “α(1) alone” channels are in fact tightly associated α(1)β3xo channels, and that effects of exogenous β subunits are due to formation of higher-order [α(1)β]β(n) complexes with an unknown contribution of β3xo. It is thus possible that functional mammalian VGCCs, rather than having subunit composition α(1)β, are [α(1)β]β(n) complexes that associate with α(2)δ and, as appropriate, other tissue-specific accessory proteins. In support of this hypothesis, we discovered that the last 277-aa of α(1E) have a β subunit binding domain. This β binding domain is distinct from the previously known interaction domain located between repeats I and II of calcium channel α(1) subunits.